Student’s Views on Learning English on TikTok Application - Hasby, Nazar; Triskaya Angrum, Alna (Universitas Nusantara PGRI Kediri, 2023)
This study aims to explore students' views of the TikTok application, which can be used as a learning medium, especially learning English relevant to generation Z. This is reinforced by previous research and some experiences from several researchers. This is driven by the fact that social media is a medium that is closely related to generation Z. This study used a qualitative method to determine students' views on learning English on the TikTok application. This study used data collection and interview methods. This research was conducted on students from private universities in the first semester of the English academic year (2022/2023). Based on data obtained during interviews with several students regarding students' views on learning English in the TikTok application and the results, most participants agreed that the TikTok application could help to learn, especially learning English. Although each application has drawbacks and constraints, the TikTok application has many benefits, including learning. Furthermore, the implications of this research are closely related to learning, especially learning English, with the hope that it help students learn English modernly.